THE MENTAL AND SENSORY SIMILE IN THE POETRY OF ABU MANSOUR AL-THAALABI’S - Salwan Mghetee Shlaka (American Journals Publishing, 2024)
The simile image is one of the elements of aesthetic formation in the text, and the simile has splendor and beauty that is well located in the soul, as it brings the distant image closer to the mind, and brings out the familiar to the unfamiliar with wit and creativity. The simile image is considered one of the argumentative tools that serve as evidence and proof in poetry, so it comes the poet created it to demonstrate an issue, or to bring something outside the mind closer to something internally familiar. Scientists have excelled in delving into its secrets and talking about its beauty.
Keywords: simile, Abu Mansour Al-Thaalabi”s mental simile and sensory simile.